Polemik Penetapan Upah Minimum Pekerja: Kebutuhan dan Gaji Minimum Yang Tidak Seimbang - Putri, Dea Kumala (Media Hukum Indonesia (MHI), 2024)
The purpose of this research is to analyze regulations in legal legislation that cover minimum wage rights for workers, namely Law Number 6 of 2024 Job Creation  concerning regulations on minimum wages for workers. This study was written using normative statutory legal techniques, namely through the results of sharp and deep thinking and based on Law No. 6 of 2024 Ciptaker. Accompanied by supporting analysis from related literature and books. This research found the final result that it turns out that Law Number 6 of 2024 on Job Creation has not been optimal in ensuring equality and welfare of workers regarding minimum wages, which ultimately gave birth to new polemics and created many social symptoms in society caused by economic factors, one of the causes of which is an imbalance between wages received and the amount of expenditure in an area.